纳米ZnO粒子对航空润滑油性能的影响 - 陈浩; 许松 (Jixie chuandong)
ZnO nanometer particles were added to aviation lubricating oil with mechanical blending means. Its antiwear effect to aviation lubricating oil was tested on a self-made friction and ware tester. The result shows that ZnO nanometer particles can improve antiwear properties greatly.